Genetic and Functional Variants Analysis of the GATA6 Gene Promoter in Acute Myocardial Infarction - Sun, Zhaoqing; Pang, Shuchao; Cui, Yinghua; Yan, Bo (Frontiers in Genetics, 2019)
Background: Acute myocardial infarction (AMI) which is a specific type of coronary artery disease (CAD), is caused by the combination of genetic factors and acquired environment. Although some common genetic variations have been recorded to contribute to the development of CAD and AMI, more genetic factors and potential molecular mechanisms remain largely unknown. The GATA6 gene is expressed in the heart during embryogenesis and is also detected in vascular smooth muscle cells (VSMCs) and different human primary endothelial cells (ECs). To date, no studies have directly linked GATA6 gene with regulation of the CAD. Methods: In this study, we used a case-control study to investigate and analyze the genetic variations and functional variations of the GATA6 gene promoter region in AMI patients and controls. A variety of statistical analysis methods were utilized to analyze the association of single nucleotide polymorphisms (SNPs) with AMI. Functional analysis of DNA sequence variants (DSVs) was performed using a dual luciferase reporter assay. In vitro, electrophoretic mobility shift assay (EMSA) was selected to examine DNA-protein interactions. Results: A total of 705 subjects were enrolled. Ten DSVs were found in AMI patients (n=352) and controls (n=353), including seven SNPs. One novel heterozygous DSV (g.22168409 A>G) and two SNPs [g.22168362 C>A(rs1416421760) and [g.22168521 G>T(rs1445501474)] were reported in three AMI patients, which were not found in controls. The relevant statistical analysis, including allele and genotype frequencies between AMI patients and controls, five genetic models, linkage disequilibrium (LD) and haplotype analysis and SNP–SNP interactions, suggested no statistical significance (P > 0.05). The transcriptional activity of GATA6 gene promoter was significantly increased by the DSV (g.22168409 A>G) and SNP [g.22168362 C>A(rs1416421760)]. The EMSA revealed that the DSV (g.22168409 A>G) and SNP [g.22168362 C>A(rs1416421760)] evidently influenced the binding of transcription factors. Conclusion: In conclusion, the DSV (g.22168409 A>G) and SNP [g.22168362 C> A(rs1416421760)] may increase GATA6 levels in both HEK-293 and H9c2 cell lines by affecting the binding of transcription factors. Whether the two variants identified in the GATA6 gene promoter can promote the development and progression of human AMI by altering GATA6 levels still requires further studies to verify.